Respuesta :

Answer:

x = 1 , x = [tex]\frac{3}{2}[/tex]

Step-by-step explanation:

2x² - 5x + 3 = 0

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 2 × 3 = 6 and sum = - 5

The factors are - 2 and - 3

Use these factors to split the x- term

2x² - 2x - 3x + 3 ( factor the first/second and third/fourth terms )

2x(x - 1) - 3(x - 1) = 0 ← factor out (x - 1) from each term

(x - 1)(2x - 3) = 0

Equate each factor to zero and solve for x

x - 1 = 0 ⇒ x = 1

2x - 3 = 0 ⇒ 2x = 3 ⇒ x = [tex]\frac{3}{2}[/tex]